2000
DOI: 10.1111/1467-9280.00259
|View full text |Cite
|
Sign up to set email alerts
|

Taxonic Structure of Infant Reactivity: Evidence From a Taxometric Perspective

Abstract: Previously, we proposed a theoretical framework that classified infants into qualitative categories of reactivity, rather than on a continuous dimension. The present research used an objective statistical procedure (maximum covariance analysis, or MAXCOV) to determine if a qualitative latent structure, consistent with our theoretical conjectures, would be found to underlie quantitative indices of reactivity to stimuli in a sample of 599 four-month-old infants. Results of the MAXCOV analysis showed clear eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 17 publications
4
58
0
Order By: Relevance
“…Sensory contributions to emotional reactivity in this colic sample are further supported by the moderate and significant inverse correlations found between hours of fussing and the Sensory Profile subtests Tactile, Auditory, Visual Processing, and Emotional Reactivity. Similar to sensory-processing theory, some authors have suggested that temperamental differences such as low sensory thresholds, reduced soothability, and increased motor activity in response to stimuli may account for emotional reactivity (Canivet et al, 2000;Carey, 1972;Rothbart, Ziaie, & O'Boyle, 1992;Woodward, Lezenweger, Kagan, Snidman, & Arcus, 2000). Many items on the Emotional Reactivity subtest of the Sensory Profile are similar to temperament questionnaires such as "cries easily, displays excessive emotional outbursts, has temper tantrums, poor frustration tolerance, and difficulty tolerating changes in routines."…”
Section: Discussionmentioning
confidence: 97%
“…Sensory contributions to emotional reactivity in this colic sample are further supported by the moderate and significant inverse correlations found between hours of fussing and the Sensory Profile subtests Tactile, Auditory, Visual Processing, and Emotional Reactivity. Similar to sensory-processing theory, some authors have suggested that temperamental differences such as low sensory thresholds, reduced soothability, and increased motor activity in response to stimuli may account for emotional reactivity (Canivet et al, 2000;Carey, 1972;Rothbart, Ziaie, & O'Boyle, 1992;Woodward, Lezenweger, Kagan, Snidman, & Arcus, 2000). Many items on the Emotional Reactivity subtest of the Sensory Profile are similar to temperament questionnaires such as "cries easily, displays excessive emotional outbursts, has temper tantrums, poor frustration tolerance, and difficulty tolerating changes in routines."…”
Section: Discussionmentioning
confidence: 97%
“…For example, there is evidence of a high-reactivity taxon in infant temperament (Woodward et al, 2000) and indications of a social anxiety disorder phenotype for high reactivity/behavioral inhibition in infants (see Kagan, 2001;Schwartz et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…For example, consistent with a taxonic (i.e., categorical) conceptualization of social anxiety disorder, behavioral inhibition (i.e., a temperament characterized by early manifested traits which endure over time; Kagan, 2001) and high infant reactivity (i.e., a proposed developmental precursor to behavioral inhibition; see Woodward, Lenzenweger, Kagan, Snidman, & Arcus, 2000), have been suggested as discrete causal factors in the etiology of this disorder (Kagan, 2001). To illustrate, a high-reactivity taxon has been identified in 4-month-old infants wherein elevated behavioral inhibition has been demonstrated in taxon class members at 4-year follow-up (Woodward et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses based on both a finite mixture model (Stern, Arcus, Kagan, Rubin, & Snidman, 1994) and maximum covariance analysis (Woodward, Lenzenweger, Kagan, Snidman, & Arcus, 2000) have shown that a categorical conception fits the 4-month data better than one that assumes a continuum of reactivity.…”
Section: Temperament Classification At 4 Monthsmentioning
confidence: 99%